Semen production traits and freezability of spermatozoa of boer grade goats - SUNDARARAMAN, M N; EDWIN, M JOHN (The Indian Journal of Animal Reproduction, 2023)
A total of 94 semen collections from two Boer Grade (Boer x Local) half-bred bucks were used to study the semen produ ction traits and freezability of spermatozoa. The semen production traits recorded in the study were Ejaculate volume (0.60±0.03 ml), Mass activity (4.55±0.07) (0 to 5 scale), sperm motility (78.19±0.94 per cent), sperm concentration (3416.00±178.66 million/ml), live spermatozoa (82.16±0.92 per cent), abnormal spermatozoa (8.43±0.66 per cent), pre-freeze motility (71.94±0.78 per cent), post-thaw motility (31.67±2.16 pe, cent) and total doses of frozen semen per collection (14.86±1.74). Highly significant (P :’c 0.01) difference was noticed between bucks for sperm concentration. Live spermatozoa also exhibited significant (P :’c 0.05) variation between bucks.